2016
DOI: 10.4103/2229-3485.179433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception regarding clinical trials among doctors of government medical colleges: A questionnaire-based study

Abstract: Aims:By virtue of being a specialized field by itself, the science of clinical trials (CTs) may not be well understood by doctors who are not specifically trained in it. A lack of knowledge may translate to a negative perception toward CT. With the idea of getting a situational snapshot, we estimated the knowledge and perception of CTs among doctors from government medical colleges of West Bengal who are not trained on CT in their postgraduate curriculum. Several determinants of knowledge and perception regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…In our study(40.8%) of students involved in clinical trials. Similar to our indings, study conducted by a Koyto et al believed most of the postgraduate students involved in clinical trials (Chatterjee et al, 2016) and according to supro Chaudhary et al-she observed 90% of doctors wanted clinical trials training to be incorporated in the undergraduate curriculum. The results of our study shows postgraduates have a better knowledge about clinical trials than the undergraduate.…”
Section: Resultssupporting
confidence: 86%
“…In our study(40.8%) of students involved in clinical trials. Similar to our indings, study conducted by a Koyto et al believed most of the postgraduate students involved in clinical trials (Chatterjee et al, 2016) and according to supro Chaudhary et al-she observed 90% of doctors wanted clinical trials training to be incorporated in the undergraduate curriculum. The results of our study shows postgraduates have a better knowledge about clinical trials than the undergraduate.…”
Section: Resultssupporting
confidence: 86%
“…The study instrument was developed via brainstorming within the research team and by referring to previous literature. 15 , 16 The initial draft of the questionnaire was face-validated via a group of experts, where input was taken and the questionnaire adjusted accordingly. Thereafter, the questionnaire was pilot-tested, where feedback from 30 participants who had been encouraged to provide comments about the clarity and comprehensibility of each item of the questionnaire was taken.…”
Section: Methodsmentioning
confidence: 99%
“…Current findings were in agreement with results from other studies done in other developing countries. 11,16,17,20 Although a large percentage of medical residents reported that they have taken training courses about clinical research at some point during their clinical training, only a small number of them showed basic knowledge about ethical standards related to patients' privacy and rights protection codes. More than two thirds of respondent residents showed adequate knowledge about informed consent importance and elements as well as when it is mandatory to be taken.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review was performed to determine the core points utilized to assess attitudes and knowledge of medical residents toward clinical trials. 16,17 The questionnaire items were tailored to suit the purposed study objectives focusing on cancer-related clinical trials. An informed consent statement was included at the beginning of the questionnaire with a brief description of the study purpose and the questionnaire participants provided their informed consent for their participation.…”
Section: Questionnairementioning
confidence: 99%